KARAKTERISTIK MORFOLOGI DAN KLASIFIKASI TANAH LUAPAN BANJIR BERULANG DI KABUPATEN KONAWE SELATAN - M. Tufaila .; Hasbullah Syaf; Jufri Karim; Lies Indriyani (Agriplus, 2014)
Land as an open system gives the space a dynamic process in the process of formation. Initial conditions of soil derived from a particular parent material, because the natural process leads to changes in the morphological characteristics of the soil. These conditions will further affect its use for the benefit of mankind. For that reason has conducted research on morphological characteristics and classification of land in outburst floods repeatedly in South Konawe. Research conducted by the survey grid of 50 m in an area of 70.73 ha and analyzed the physical and chemical properties, to acquire land map unit (LMU). At every LMU obtained conducted intensive observation. Three LMU generated described and each horizon soil samples were taken for analysis of physical and chemical properties. The results showed that all three Pedon were observed have a very deep to depth of solum category (> 100 cm); ground color varies; texture of clay, loam, clay loam dusty; firm consistency; angular blocky soil structure. This indicates that there has been mixing topsoil by outburst floods, however horizon B down comes from the same parent material. Soil characteristics indicate that the land is very acid reaction to acid, available nutrients (N, P and K) and exchangeable base cations, cation exchange capacity (CEC) is very low to low, base saturation (BS) is very low to moderate. This soil is classified in the great group as Dystrudepts, Hapluduts and Hapluduts.   Keywords:  vharacteristic, morphology, classification,  and land outburst floods